2014
DOI: 10.1371/journal.pone.0086416
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Lactobacillus plantarum Strain AYA Enhances IgA Secretion and Provides Survival Protection against Influenza Virus Infection in Mice

Abstract: The mucosal immune system provides the first line of defense against inhaled and ingested pathogenic microbacteria and viruses. This defense system, to a large extent, is mediated by the actions of secretory IgA. In this study, we screened 140 strains of lactic acid bacteria for induction of IgA production by murine Peyer’s patch cells. We selected one strain and named it Lactobacillus plantarum AYA. We found that L. plantarum AYA-induced production of IL-6 in Peyer’s patch dendritic cells, with this productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 29 publications
(31 reference statements)
4
76
0
2
Order By: Relevance
“…For example, they can downregulate proinflammatory cytokines by inhibiting proinflammatory nuclear factor jB and increasing expression of cytoprotective heat shock proteins [56], inducing mucosal immunoglobulin A production and providing protection against respiratory influenza virus infection [57], restoration of the gliadin-induced epithelial barrier disruption and enhancing intestinal epithelial integrity [58], and affecting pain perception and gut motility by targeting sensory nerves in the nervous system [59].…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%
“…For example, they can downregulate proinflammatory cytokines by inhibiting proinflammatory nuclear factor jB and increasing expression of cytoprotective heat shock proteins [56], inducing mucosal immunoglobulin A production and providing protection against respiratory influenza virus infection [57], restoration of the gliadin-induced epithelial barrier disruption and enhancing intestinal epithelial integrity [58], and affecting pain perception and gut motility by targeting sensory nerves in the nervous system [59].…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%
“…This result is in good agreement with that of our previous study. 1) We have demonstrated that L. plantarum AYA induces IL-6 production in dendritic cells, separated from Peyer's patch cells, and that IL-6 production induces IgA production.…”
mentioning
confidence: 86%
“…It has been reported that the AYA strain of Lactobacillus plantarum (FERM P-21106) increases IgA production in murine Peyer's patch cells, 1) and oral administration of L. plantarum AYA in mice causes an increase in IgA production in the small intestine and lungs. 1) IgA production may provide primary immune protection to the mucosa and correlates strongly with immune protection; the treated mice survived longer than control mice after lethal influenza virus infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of strains of L. plantarum have shown positive health benefits to the host in animal studies and human clinical trials, with particular regard to immune health. These benefits include stimulation of IgA production and murine protection from influenza infection when administered orally, production of bacteriocins that effectively prevent growth of pathogens, such as M. tuberculosis, downregulation of inflammatory cytokines IL-6 and IL-12, and upregulation of the antiinflammatory cytokine IL-10 (Citar, 2014;Kikuchi, 2014;Todorov, 2014). Immune system modulation was further demonstrated in clinical trials in which L. plantarum was used as a treatment for Japanese Cedar Pollinosis (JCP), with alleviation of allergenic symptoms by induction of anti-inflammatory IL-10 (Harima-Mizusawa, 2014), and also for atopic dermatitis in children, with significant improvement in symptoms and a decrease in INF-γ, IL-4 and eosinophils (Han, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 passage through the gastrointestinal tract; and fecal chemical analyses for bile acids, neutral sterols, SCFAs, branched chain fatty acids (BCFAs), and lactic acid.…”
Section: Introductionmentioning
confidence: 99%